Implementation of the Independent Curriculum in Digital Literacy Training for Interactive Learning Media to Improve Pedagogic Competencies of Teachers in MTsN Gowa Regency - Zaenab Zaenab; Samsudi Samsudi; Isti Hidayah; Agus Wahyudin (International Conference on Science, Education, and Technology, 2023)
The existence of the Covid-19 pandemic has had a major impact on various sectors in Indonesia, one of which is education. In the new era, education is important to improve human resources. The rapid development of technology will change the way people move and work. The presence of technology as part of society's needs will further reinforce insight into technology. And the Independent Curriculum provides flexibility for educators to improve the quality of education according to the needs of students, so the use of technology in education must be seen as a way to encourage the improvement of the quality of education in this era. In facing the rapid development of technology, digital literacy is the main key and foundation that must be owned by educators. One of the problems faced by teachers is the difficulty of using digital platforms for learning. With limited mastery of technology for learning, it is an initiative for schools to organize training as an effort to increase teacher digital literacy. The purpose of this training activity is to provide interactive learning media training to improve the digital literacy of MTsN teachers in Gowa Regency. The method in this activity is carried out in three stages: pre-training, training implementation, and post-training. Indicators of the success of the activity can be seen from (1) the positive response from the participants regarding this training and (2) the existence of interactive learning media products made by the participants. The results of this training activity showed (1) there was an increase in participants' understanding of interactive learning media with an average of 77% and categorized as very good and, (2) participants were able to make quizzes using interactive learning media.